Sustainable energy generation from plastic waste: An in-depth review of diesel engine application - Yagoob, Haseeb; Tan, Ee Sann; Ali, Hafiz Muhammad; Ong, Hwai Chyuan *; Jamil, Muhammad Ahmad; Farooq, Muhammad Umer (Elsevier, 2024)
Plastic consumption has increased significantly over the previous few decades and it is one of the most significant sources of waste in many countries. Recycling and energy recovery methods are just two methods for dealing with plastic waste. As a result, the process of converting waste plastic into energy and its application in the diesel engine was reviewed in the present study. The pyrolysis process could be utilized to use plastic waste efficiently. The waste plastic is converted to liquid oil, gas, and solid by using this process. This article reviewed the application of plastic pyrolysis oil (PPO) in diesel engines regarding its properties and effects on the fuel's performance, combustion, and emission parameters. PPO typically has a lower sulfur concentration than standard diesel fuel. Plastic pyrolysis oil (PPO) improves cylinder pressure, brake power, and brake thermal efficiency while lowering fuel consumption when blended with diesel. Emissions can also vary depending on combustion characteristics, fuel quality, and engine technology. The literature on emission assessments yields conflicting results regarding nitrogen oxides and hydrocarbon emissions from PPO. However, because of the higher oxygen concentration, carbon monoxide (CO) and particulate matter (PM) often decrease. Finally, the study recommended a 10%− 90% mix of PPO-diesel as an alternative fuel for the engine with no modifications; this concentration may be increased by adding additives/nanoparticles in the fuel or modifying the engine.